Perceptions of processed foods as unhealthy: Heuristic strength, prevalence, and potential implications for the protein shift - Elizabeth S. Collier; Kathryn L. Harris; Marcus Bendtsen; Hanieh Moshtaghian; Susanne Bryngelsson; Jun Niimi (Future Foods)
Plant-based analogues (PBAs) for meat and dairy are typically categorised as ultra-processed foods. However, current evidence that PBA consumption negatively impacts health is controversial. As such, these products may be inappropriately negatively coloured by the “processed foods are unhealthy” heuristic. We investigated the strength of this heuristic among Swedish consumers and explored its impact on perceived healthiness within different food categories (meat, dairy, seafood, vegetables/legumes, and PBAs). In an online experiment, participants (N=563) rated the healthiness and level of processing of 24 food products (presented as images), completed the food technology neophobia (FTN) scale, and reported consumption frequency of different foods. The results indicated that this heuristic, measured as Pearson's r between perceived healthiness and level of processing, was prevalent and robust (posterior mean = -0.58, probability of association>99 %) as well as stronger among women and individuals with higher FTN. Moreover, the impact of the heuristic differed across food categories: healthiness ratings for vegetable/legume and seafood products perceived as processed were more negatively impacted compared to those for meat products (probability of association>99 %). The potential implications of this for the protein shift and encouraging substituting red meat with products based on raw materials associated with health (i.e., plants and seafood) are discussed.